Leadership Perspective Employee Satisfaction Analysis - Mugira, Ahmad (AKADEMIK: Jurnal Mahasiswa Humanis, 2022)
Work standard is a management instrument in ensuring the running of an activity effectively. However, as humans, employees have feelings, so attitudes and work behavior are strongly influenced by emotional factors (satisfied/happy). One source of employee satisfaction is leadership. The good attitude and behavior of leaders towards employees, has a positive impact on the psychological state of employees. So not infrequently, a good leadership model can turn on a pleasant productive work environment. In order to answer this phenomenon, a qualitative approach with descriptive analysis is used. The research subjects were lecturers of private universities in Banten province, totaling 200 people. Data collection was done at simple random with a questionnaire as a research instrument. The results of the study obtained information, that the lecturers were not happy if the head of the study program did not / did not act fairly in terms of the distribution of academic activities. This condition can cause a decrease in discipline and work commitment, so that it has an impact on the performance of the lecturers' tri dharma. Another thing that makes lecturers dissatisfied is about the attitude of the leadership, there is a tendency to be more in favor of the interests of the university by ignoring the interests of employees. This causes feelings of disappointment.